A rare homozygous variant of CHKB induced severe cardiomyopathy and a cardiac conduction disorder: a case report - Jing, Siyuan; Liu, Lu; Li, Yifei; Liu, Fuqiang; Hua, Yimin; Duan, Hongyu (Frontiers in Cardiovascular Medicine, 2024)
The CHKB gene plays a crucial role in regulating mitochondrial function and choline metabolism. Mutations in CHKB lead to conditions like megaconial congenital muscular dystrophy (MCMD), characterized by enlarged mitochondria and impaired mitochondrial function, inducing various clinical features in neurological and cardiac performances. Herein, we reported a rare case presenting dilated cardiomyopathy (DCM) as dominant feature with a homozygous nonsense variant of CHKB and related therapeutic strategy.The proband, a 13-year-old male, presented with a complex clinical profile characterized by mild intellectual disability and severe cardiac impairment, including reduced activity tolerance, suspected acute heart failure, significant cardiac enlargement, left anterior fascicular block and complete right branch bundle block. WES identified a homozygous nonsense variant had been identified as c.598delC (p.Q200Rfs*11) of CHKB gene, resulting in disease causing by amino acid sequence changed, protein truncated and splice site changes by MutationTaster analysis. The protein structure of CHKB had been built and named AF-Q9Y259-F1. The residues around 200 site of amino acid changed in CHKB p.Q200Rfs*11 with unaltered hydrogen bond which indicated the pathogenic of such variant mainly originated from truncated protein induced by the nonsense mutation. The heart blocks in the proband were considered to be associated with choline metabolic impairment, and it would benefit the patient with cardiac resynchronization therapy. While, missense homozygous or compound heterozygous variants, as well as the missense and nonsense combined compound heterozygous variants of CHKB usually led to neurological impairments and muscular weakness. Conclusion: This study expands the spectrum of CHKB mutations and provides essential information for the genotype-phenotype map of a nonsense variant of the gene. It is important to make a confirmed differential diagnosis among such patients with WES analyses. Regular cardiac and musculoskeletal monitoring is recommended for MCMD patients. Patients with CHKB deficiency presenting with heart blocks could benefit from cardiac resynchronization therapy administration. This therapeutic Deleted: was 55 approach might improve cardiac function and conduction in patients with CHKBrelated cardiomyopathies.